Research Productivity and Citation Analysis of Indian Institute of Technology, Madras: An Overview - MT, Basavaraja; ., Chimmoji; SC, Prashantha (Journal of Advanced Research in Library and Information Science, 2020)
Metrics studies increasingly used to assess the quantity and quality of scientific research output in many research fields worldwide. This study aimed to evaluate the research productivity of the Indian Institute of Technology, Madras. To identify the Research productivity of the Indian Institute of Technology, Madras, the Web of Science database was used. Records were searched in database published between 1989 and 2018. The contributions of faculty members were evaluated based on the publication, total number of citations, average citations and h-index. The result of the study found that majority (8.90%) of articles have been published in the year 2018, 90.28% of articles are included in the Web of Science, 16.37% of records related to Materials Science Multidisciplinary subject and 8.18% of records have been published by the faculty members with the collaboration of faculty members of Council of Scientific Industrial Research (CSIR) India among top 10 organisations. The study also found that Gosh S, has highest publications (487) and secured 1st rank followed by Choi Y, (430) and Hou W.S. (417) secured 2nd and 3rd rank respectively.